Emerging Concepts in the Evaluation and Management of Takayasu Arteritis:New Wine in an Old Bottle - Durga Prasanna Misra; Vikas Agarwal (Dr. Annil Mahajan, 2022)
Takayasu arteritis is an enigmatic granulomatous large vessel vasculitis more common in the Indian scenario than in the West. Takayasu arteritis associates with impaired quality of life and also increases the risk of dying. Takayasu arteritis can present to virtually any medical or surgical specialty. In this editorial, we overview emerging concepts in the evaluation and management of Takayasu arteritis.